2020
DOI: 10.3390/ijms21093266
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Mitochondrial Morphology and Function in the BTBR Mouse Model of Autism Is Improved by Two Weeks of Ketogenic Diet

Abstract: Autism spectrum disorder (ASD) is a highly prevalent neurodevelopmental disorder that exhibits a common set of behavioral and cognitive impairments. Although the etiology of ASD remains unclear, mitochondrial dysfunction has recently emerged as a possible causative factor underlying ASD. The ketogenic diet (KD) is a high-fat, low-carbohydrate diet that augments mitochondrial function, and has been shown to reduce autistic behaviors in both humans and in rodent models of ASD. The aim of the current study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 80 publications
(115 reference statements)
4
30
0
Order By: Relevance
“…Therefore, understanding the mitochondrial mechanisms involved in ASD could be important for the identification of new targets in the treatment of pathology. Regarding this topic, a very recent study evaluated the mitochondrial bioenergetics in the BTBR mouse model of ASD [49]. The authors investigated changes in mitochondrial morphology, which can directly influence mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding the mitochondrial mechanisms involved in ASD could be important for the identification of new targets in the treatment of pathology. Regarding this topic, a very recent study evaluated the mitochondrial bioenergetics in the BTBR mouse model of ASD [49]. The authors investigated changes in mitochondrial morphology, which can directly influence mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Complex II activity was reduced, and a fragmented mitochondrial shape was found in neocortical tissue. The mitochondrial phenotype in this model could be reversed by administering a ketogenic diet (KD) [ 181 ]. BTBR mice fed with KD for 14 days showed discrete changes in the mRNA expression of mitochondrial bioenergetic transcripts in the hippocampus and temporal cortex [ 182 ].…”
Section: Asd-related Neurodevelopmental Disordersmentioning
confidence: 99%
“…al 2018 [ 184 ] Reduced oxygen consumption, reduced SOD activity, increased ROS production BTBR mice Isolated mitochondria from hippocampus, hippocampus Ahn et. al 2020 [ 181 ] Reduced oxygen consumption, round shape mitochondria, increased expression of phosho-Drp1 at Ser616 and phospho-Mff at Ser146 BTBR mice Isolated mitochondria from Neocortex, primary cortical neurons Bentea et. al 2020 [ 190 ] Reduced presynaptic mitochondrial population xCT -/- mice Striatum Janickova et.…”
Section: Asd-related Neurodevelopmental Disordersmentioning
confidence: 99%
“…Only recently, they were characterized as having an autism-like behavioral phenotype [ 20 , 21 ]. They show a robust ASD phenotype being characterized by the three main symptoms: impaired sociability, communication deficits and repetitive behaviors [ 22 , 23 ]. Moreover, C57BL/6J (B6) mice models are available as the control strain for research using BTBR mice [ 24 , 25 , 26 ] and this has made it possible to use these models as the basis for many studies.…”
Section: Introductionmentioning
confidence: 99%
“…Other components within the mucous gel include water, electrolytes, sloughed epithelial cells and secreted immunoglobulins. Mucus produces a physical and chemical barrier that protects the epithelium from physical damage by luminal content, guards against bacterial invasion, regulates epithelial hydration, and interacts with secreted immunoglobulin A to produce antibody and antitoxin effects [ 23 , 31 , 32 ]. Recently, Yang and Yu [ 33 ] indicated that the perspective regarding GCs and their products has changed, suggesting that they are not passive cells but play a positive role in maintaining intestinal tract immunity and mucosal homeostasis.…”
Section: Introductionmentioning
confidence: 99%